Studi Tentang Kebijakan 4S di PT XYZ Pada Part Business Operation Division - Okta Armelya Rahim; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (CV. Aksara Global Akademia, 2023)
This research used a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The aim of this research is to determine the application of 4S principles by vocational employees at PT From the results of this research, it can be seen that PT This can be seen from the lack of implementation of other 4S aspects.